2019
DOI: 10.3808/jeil.201900012
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Long-Term Near-Surface Temperature Based on NA-CORDEX Output

Abstract: Temperature is one of the most important parameters in climate modeling, as it has significant impacts on various geophysical processes such as evaporation and precipitation. Applying multiple climate models for prediction generally outperforms the use of individual climate models, and neural networks perform well at capturing nonlinear relationships, which can provide more reliable temperature projections. In this study, three neural network algorithms, including Multi-layer Perceptron (MLP), Time-lagged Feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, climate change projections generated by different GCMs are uncertain, since each GCM has been developed based on its own assumptions and unique mathematical representations of physical climate system processes (Zhuang et al ., 2016). Due to the enormous uncertainty caused by the choice of a single GCM, the use of multi‐GCM ensembles has been widely used for a realistic assessment of climate change (Chilkoti et al ., 2017; Her et al ., 2019; Li et al ., 2019). Multi‐GCM ensembles are able to provide more comprehensive simulations of climate variables than the use of individual climate models (Li et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, climate change projections generated by different GCMs are uncertain, since each GCM has been developed based on its own assumptions and unique mathematical representations of physical climate system processes (Zhuang et al ., 2016). Due to the enormous uncertainty caused by the choice of a single GCM, the use of multi‐GCM ensembles has been widely used for a realistic assessment of climate change (Chilkoti et al ., 2017; Her et al ., 2019; Li et al ., 2019). Multi‐GCM ensembles are able to provide more comprehensive simulations of climate variables than the use of individual climate models (Li et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ensemble modeling was a key technology to project drought population exposure (J. Li et al., 2020; X. Li et al., 2020). Many studies have indicated the advantages of ensemble modeling (Li et al., 2019). In recent years, economic construction and human production in the PRB have been affected dramatically by climate change, especially extreme climate events.…”
Section: Introductionmentioning
confidence: 99%